Efektivitas Metode Pembelajaran Story Telling Terhadap Hasil Belajar Siswa SDN 19 Rambang Niru, Muara Enim - Shella Zuliana; Sylvia Lara Syaflin; Kabib Sholeh (Elementary Teacher Education Program, Majalengka University, 2023)
This research is motivated by the problems that occur, namely the learning process does not involve students, student responses are not too focused so it is difficult to understand learning. This is due to the use of inappropriate methods where the teacher only uses conventional learning methods, namely lectures, which results in low student learning outcomes, especially in Civics lessons. This study aims to determine whether or not the Story Tellinglearning method is effective for student learning outcomes at SDN 19 Rambang Niru, Muara Enim. The method used by researchers is a quasi-experimental method with a nonrandomized control group pretest-posttest design. Data collection techniques using observation, tests, and documentation. Data analysis used normality test, homogeneity test, N-gain test, Independent sample t-test (t-test). Based on the results of this study, data analysis and discussion are proven by calculating the N-gain test showing that the calculation results obtained values of 76, 1529 or > 76, which means that the Story Tellinglearning method is effectively used compared to conventional learning methods. And the results of the calculation of the t-test with a significant level of 0.05 obtained the results of an important degree of 0.000 which is smaller than the sig value of 0.05 meaning 0.000 <0.05. The results showed that Ho was rejected and Ha was accepted, meaning that there was an effectiveness of the Story Tellinglearning method on student learning outcomes at SDN 19 Rambang